1994
DOI: 10.1002/hup.470090105
|View full text |Cite
|
Sign up to set email alerts
|

Precision of measures of saccadic eye movements and conventional psychomotor function tests

Abstract: Measures of variability are rarely quoted in drug studies of psychomotor function. Five recent studies were therefore analysed to calculate the coefficients of variation for different tests of psychomotor function, both during and between study days. Saccadic eye movement analysis and critical flicker fusion threshold were found to have low coefficients of variation (ranging from 2.7 to 7.5 per cent) while visual analogue rating scales and the digit symbol substitution test were found to have much higher coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
(3 reference statements)
2
3
0
Order By: Relevance
“…This is consistent with previous studies which indicate that psychophysiological measures such as PSV have better reliability and consistency than those with more subjective components (Mannion et al 1994). The variation may also in part be due to the presence of adverse e¤ects within the haloperidol 6 mg group; good results were obtained from the 2 mg and 4 mg groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with previous studies which indicate that psychophysiological measures such as PSV have better reliability and consistency than those with more subjective components (Mannion et al 1994). The variation may also in part be due to the presence of adverse e¤ects within the haloperidol 6 mg group; good results were obtained from the 2 mg and 4 mg groups.…”
Section: Discussionsupporting
confidence: 92%
“…While haloperidol is a relatively less sedating antipsychotic, it is observed to have a sedative e¤ect clinically and subjects do complain of sedation as a side e¤ect in healthy volunteer studies (King et al 1995). The clear and internally consistent PSV Þndings in this study tend to support the contention that the objectivity and low variability of PSV may allow it a measure of advantage over subjective measures such as VARS (Mannion et al 1994;Green et al 1996).…”
Section: Discussionsupporting
confidence: 65%
“…VARS have been shown to be a sensitive measure in the past, but the intrinsic subjectivity of this test is of concern if it is used as the only measure of sedation in a study where measurement of relative levels of sedation is crucial to correct interpretation of the results. Measurement of the coefficient of variation of a range of psychomotor tests shows that peak saccadic velocity has a greater precision and reliability than VARS, DSST, choice reaction time or a derivative (Bond and Lader 1974) of the Norris VARS (Roy-Byrne et al 1993;Mannion et al 1994). Tests that incorporate an information processing or cognitive component had a higher coefficient of variation both within a study day and over the duration of a study.…”
Section: Discussionmentioning
confidence: 97%
“…Tests that incorporate an information processing or cognitive component had a higher coefficient of variation both within a study day and over the duration of a study. Mannion et al (1994) therefore concluded that a psychophysiological measure such as peak saccadic velocity should always be included in a psychomotor test battery if the neurophysiological status of the brain is likely to be altered, e.g., by sedation.…”
Section: Discussionmentioning
confidence: 98%
“…The targets for saccades were presented at a fixed interval of 1.5 s (0.66 Hz), and were modelled on an angle of 35°. The principal measure was peak saccadic velocity (PSV) which, in our hands, has a coefficient of variation of between 2.9 and 4.3 % (Mannion, Lynch and King, 1994).…”
Section: Critical Flicker Fusion Threshold (Cfft)mentioning
confidence: 99%